REVIEW: The ethnobotany of ferns and fern allies - Prance, G. T. (2015)
A summary is presented of the most important ways in which ferns have been important to humanity. Many of these categories are positive such as the use of ferns for subsistence. On the negative side is their role as weeds and as bearers of substances harmful to human health. Many of the traditional uses such as for medicines have been transferred to modern life as societies have modernized. Some uses have even become important in industrial society, for example in the assay of new medicines.